Synthesis and characterization of microwave-hydrothermally derived Ba1-xSrxTiO3 powders - Deshpande, S. B.; Khollam, Y. B.; Bhoraskar, Y. B.; Date, Sadgopal K.; Sainkara, S. R.; Potdar, H. S. (Materials Letters, 2005)
Submicron-sized, spherical, stoichiometric strontium substituted barium titanate: Ba0.75Sr0.25TiO3 (BST) powders are prepared by microwave-hydrothermal (MH) route under the MH conditions of 200 degreesC, 200 psi, and 30 min in strongly alkaline conditions (pH>12) using potassium titanyl oxalate (KTO) and nitrates of Ba and Sr as the starting precursors and KOH as the mineralizer. The characterization studies by XRD, XRF and SEM indicated that stoichiometric cubic BST powders (a(0)=3.992 A) were obtained by adjusting MH conditions mentioned earlier and keeping the (Ba+Sr)/Ti ratio in starting solution slightly in excess (similar to1.06). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; dissolution-recrystallization; Microstructure; microwave-hydrothermal synthesis; mineralizer; SEM; XRD; XRF